The optimal orthodontic displacement of clear aligner for mild, moderate and severe periodontal conditions: an in vitro study in a periodontally compromised individual using the finite element model - Yanning Ma; Song Li (BMC, 2021)
Abstract Background Pathologic tooth migration (PTM) is a common complication of mild to severe periodontitis and proper orthodontic treatment is helpful to alleviate periodontal diseases. The goal of this study is to explore an optimal orthodontic displacement of clear aligner using a three-dimensional (3D) finite element model (FEM). Methods The cone beam computed tomography (CBCT) data of a patient received invisible orthodontics without diabetes and other systemic diseases were collected. Based on the new classification scheme for periodontal diseases in 2017 (stage I: mild periodontitis, [M1]; stage II: moderate periodontitis, [M2]; stage III: severe periodontitis, [M3]), 3D-FEMs of mandible were established using MIMICS 10.0 and ABAQUS 6.5 softwares. The 3D stress distribution diagrams and stress value of the teeth (left lower incisor, left lower central incisor, right lower lateral incisor, and right lower central incisor) under three different periodontal conditions (M1, M2, and M3) with axial inclination 90° and 100° were obtained by ABAQUS 6.5. Results The stress of anterior teeth was concentrated in the teeth neck, and became greater when the periodontal condition was worse. The stress value of anterior teeth and the strain at the top of the alveolar crest are greater as the displacement increasing. The stress value of anterior teeth and the strain at the top of the alveolar crest in axial inclination 100° are relatively great compared to those of axial inclination 90°. For patients with excessively inclined anterior teeth (such as 100°), the optimal orthodontic displacement is 0.18 mm. In order to ensure that alveolar ridge crest is not deformed, the displacement is less than 0.18 mm (strain for 0.165 mm), 0.15 mm (strain for 0.167 mm) and 0.10 mm (strain for 0.117 mm) respectively when alveolar bone is normal, resorption 1/3 or 1/3-1/2. Conclusions The optimal orthodontic displacement for patients (M1, M2, and M3) with excessively inclined anterior teeth (axial inclination 100°) is 0.18 mm. To avoid the strain at the top of the alveolar crest, the optimal displacements for M1, M2 and M3 periodontal disease patients are less than 0.18 mm, 0.15 mm and 0.10 mm, respectively.